The science helping athletes to beat the heat - O`Meara, S. (Nature, 2021)
When Scottish distance runner Callum Hawkins collapsed in the 30 °C heat of Australia`s Gold Coast while leading the marathon at the 2018 Commonwealth Games, he was left on the roadside for several minutes before paramedics came to his aid. A delay of a few minutes might seem slight, but if heat exhaustion is not treated rapidly it can have dire consequences. Just a few months later, American football player Jordan McNair died as a result of heatstroke sustained during practice at the University of Maryland in College Park. An investigation revealed that staff at the university waited more than an hour before calling an ambulance, during which time they failed to adequately cool his body. The challenges associated with exercising in extreme environments have been studied since at least the 1930s, says Paul Hough, a sports scientist at St Mary`s University in Twickenham, UK. For many years, athletes not used to competing in hot conditions have trained in warmer climates to acclimatize and reduce the risk of heat illness. Over time, strategies have been refined in the laboratory to offer more precise and evidence-based advice. "What the last 30 years of sports-science research has done is to better understand the physiological and psychological mechanisms at play," Hough says. Despite this progress, heat is only becoming more of an issue in sport, says Sébastien Racinais, head of research at Aspetar, an orthopaedic and sports-medicine hospital in Doha, Qatar. Climate change is bringing more frequent and longer spells of hot weather, and hot regions such as the Persian Gulf and East Asia are playing host to international sporting events more regularly. The next Olympic Games, scheduled to take place in Tokyo in July, could be the hottest on record, Racinais says. More effective and personalized heat-acclimatization strategies are important. But event organizers must also take steps to minimise heat exposure and provide rapid care when necessary.